STRATEGI INOVATIF UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN DI ERA DIGITAL - Oktavia, Dinda Tri; Apriyanti, Dwi; Qanita Nara, Dinda; Nazwa Nilu, Serlita; Margareta, Natashia; Sudharsono, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This journal proposes innovative strategies to enhance the quality of learning in the digital era, focusing on learning models such as blended learning, distant learning, and mobile learning. Specifically, attention is directed towards digital-era learning design and teacher understanding. An integrative approach that combines key elements from these three learning models is suggested to create holistic and sustainable learning experiences. Through in-depth analysis of the challenges and opportunities in adopting digital learning approaches, this journal offers a comprehensive framework to guide the implementation of these innovative strategies. Emphasis is placed on empowering teachers through relevant training and appropriate technological support to optimize the use of digital tools and resources in the learning context. Practical implications and theoretical contributions of this approach are also discussed, aiming to enhance learning effectiveness in the digital era.